Perilaku dan Pengetahuan Pengolahan Makanan Ibu Rumah Tangga di Kelurahan Patemon Kota Semarang - Putriningtyas, Natalia Desy; Cahyati, Widya Hary; Siyam, Nur; Farida, Eko; Maulidah, Heni (Jurnal Gizi, 2022)
The food is handled by individuals, thereby increasing the chances of food contaminationdue to improper handling. Deliberating or accidental contamination of food might endangerthe health. The purpose of this study was to evaluate the food safety knowledge, attitudes,and practices among housewives. The study was conducted using quasi experiment with aone group pretest posttest group design. The research respondents involved 41 housewiveswho live in RT 4 RW 1, Patemon Village, Gunungpati District, Semarang City. Therespondent filled questionnaire and have trained about sanitation, hygienic and how tomanage the food. The questionnaire was structure into distinctive parts to collectinformation on knowledge on food safety, attitudes towards food safety and food hygienepractices. In our study, the food-handlers were knowledgeable about hygienic practices,cleaning and sanitation procedures, such as hand washing, using gloves and proper cleaningof the utensils. In generally, the housewives have satisfactory knowledge in food safety.Key words: food, behavior, hygiene, sanitation